2015
DOI: 10.1016/j.quascirev.2015.02.011
|View full text |Cite
|
Sign up to set email alerts
|

New constraints on late Holocene eustatic sea-level changes from Mahé, Seychelles

Abstract: Citation for published item:oodro'eD F eF nd vongD eF tF nd wilneD qF eF nd fryntD gF vF nd homsD eF @PHISA 9xew onstrints on lte roloene eustti seElevel hnges from wh¡ eD eyhellesF9D uternry siene reviewsFD IIS F ppF IEITF Further information on publisher's website: httpXGGdxFdoiForgGIHFIHITGjFqusirevFPHISFHPFHII Publisher's copyright statement: NOTICE: this is the author's version of a work that was accepted for publication in Quaternary Science Reviews. Changes resulting from the publishing process, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 82 publications
(102 reference statements)
0
47
0
Order By: Relevance
“…It is useful to also compare the timing and chronology of Holocene ESL in the final 643 model to estimates made from other global far-field sites. In a recent study 644 (Woodroffe et al, 2015) where RSL predictions from the final model and ICE5G 645 were compared to sea level data from the Seychelles, it was concluded that the ESL 646 rise over the last 2 kyr was less than 2 m and that the observed RSL signal was more 647 compatible with the results of our final model. Milne and Peros (2013) that would not contribute to a sea-level rise (Fig.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…It is useful to also compare the timing and chronology of Holocene ESL in the final 643 model to estimates made from other global far-field sites. In a recent study 644 (Woodroffe et al, 2015) where RSL predictions from the final model and ICE5G 645 were compared to sea level data from the Seychelles, it was concluded that the ESL 646 rise over the last 2 kyr was less than 2 m and that the observed RSL signal was more 647 compatible with the results of our final model. Milne and Peros (2013) that would not contribute to a sea-level rise (Fig.…”
mentioning
confidence: 74%
“…9). 504 (We note that this model has been referred to in previous publications as EUST3 505 (Milne and Peros, 2013;Woodroffe et al, 2015). As Fig.…”
Section: 4: Determining An Optimal Esl Model 431 432mentioning
confidence: 99%
“…Stable islands off the coast of southern Africa (Mauritius, Reunion and Mayotte) record no highstand (with RSL stabilizing at present level by 3 ka) because these small atoll islands subside with the ocean floor from hydro-isostatic loading [44,146,147]. A recent study of late Holocene RSL in the Seychelles [148], a location demonstrated to closely measure eustatic sea level [39], showed RSL rising <2 m in the last 2 ka.…”
Section: Africamentioning
confidence: 99%
“…Presently, the relationship of sea-level change and coastal vegetation (especially mangrove) evolution has been studied by many researchers (e.g. Engelhart et al, 2007;Gonzaĺez and Dupont, 2009;Franç a et al, 2012;Woodroffe et al, 2015;Hendy et al, 2016). However, studies on the long-term dynamics of coastal vegetation, coupled with climate change and river evolution, are sparse.…”
Section: Introductionmentioning
confidence: 99%